Green Synthesis of Transition-Metal Nanoparticles and Their Oxides: A Review - Drummer, Sean (Materials (Basel), 2021)
In recent years, many researchers have begun to shift their focus onto the synthesis of nanomaterials as this field possesses an immense potential that may provide incredible technological advances in the near future. The downside of conventional synthesis techniques, such as co-precipitation, sol-gel and hydrothermal methods, is that they necessitate toxic chemicals, produce harmful by-products and require a considerable amount of energy; therefore, more sustainable fabrication routes are sought-after. Biological molecules have been previously utilized as precursors for nanoparticle synthesis, thus eliminating the negative factors involved in traditional methods. In addition, transition-metal nanoparticles possess a broad scope of applications due to their multiple oxidation states and large surface areas, thereby allowing for a higher reactivity when compared to their bulk counterpart and rendering them an interesting research topic. However, this field is still relatively unknown and unpredictable as the biosynthesis of these nanostructures from fungi, bacteria and plants yield undesired diameters and morphologies, rendering them redundant compared to their chemically synthesized counterparts. Therefore, this review aims to obtain a better understanding on the plant-mediated synthesis process of the major transition-metal and transition-metal oxide nanoparticles, and how process parameters—concentration, temperature, contact time, pH level, and calcination temperature affect their unique properties such as particle size, morphologies, and crystallinity.